Land ownership transformation before and after forest fires in Indonesian palm oil plantation areas. Issue 1 (2nd January 2019) - Purnomo, Eko Priyo; Ramdani, Rijal; Agustiyara; Tomaro, Queenie Pearl V.; Samidjo, Gatot Supangkat
ABSTRACT: Forest fires in Indonesia continue to pose as an alarming governmental, environmental, and societal concern. This study examines the context of land ownership transformation mainly before and after forest fires in palm oil plantation activities. The data were gathered through in-depth interviews, observation, and Geographical Information System (GIS) mapping. The majority of land transformations occurred from community property ownership to ownership by local elites, while the transformation from company to community and local elites was also found. Due to the injustice of land distribution, local communities occupy open access lands of companies' concessions. The deliberate use of fire is a common method among smallholder to clear land for oil palm and for sold for profit as planted land. Local elites benefit from these land transformations; however, smallholders are at an economic disadvantage. We argue that forest devolution and a clear definition of community land boundaries are critical in dealing with this issue.